Studi Literatur Potensi Pengembangan Produk Biosimilar untuk Pengobatan Penyakit Tidak Menular di Indonesia - Gizca Ratna Tazkia; Dina Mulyanti (UNISBA Press, 2022)
Abstract. The development of the era of globalization in Indonesia has resulted in an epidemiological transition that has led to an increase in the prevalence of cases of non-communicable diseases. One of the biotechnology-based treatments that can be used as a treatment for non-communicable diseases is biosimilar products. Biosimilars are products made from biological materials that have a high similarity with the originator’s biologic drugs. The purpose of this study was to determine biosimilar products that have the potential to be developed in Indonesia as a treatment for non-communicable diseases based on the highest prevalence of disease. The research method was carried out in the form of SLR (Systematic Literature Review). The results of the study indicate that there are fifteen biosimilar products that have the potential to be developed in Indonesia as the treatment of non-communicable diseases, including bevacizumab, trastuzumab, pegfilgrastim, filgrastim, epoetin alfa, insulin glargine, etanercept, infliximab, rituximab and adalimumab, teriparatide, follitropin alfa, ranibizumab, somatropin and IFN beta 1-α. Each of these biosimilar products is used for the treatment of lung cancer, HER-2 positive breast cancer, neutropenia, anemia due to chronic kidney disease, diabetes mellitus, rheumatoid arthritis, osteoporosis, infertility, neovascular age-related macular degeneration, growth hormone deficiency and multiple sclerosis. Abstrak. Berkembangnya era globalisasi di Indonesia mengakibatkan terjadinya transisi epidemiologi yang menyebabkan peningkatan prevalensi kasus-kasus penyakit tidak menular. Salah satu pengobatan berbasis bioteknologi yang dapat digunakan sebagai pengobatan penyakit tidak menular yaitu produk biosimilar. Biosimilar adalah produk yang dibuat dari bahan biologis yang memiliki kemiripan tinggi dengan obat biologis yang sudah memiliki izin atas penggunaannya. Tujuan penelitian ini untuk mengetahui produk biosimilar yang berpotensi untuk dikembangkan di Indonesia sebagai pengobatan penyakit tidak menular berdasarkan prevalensi penyakit tertinggi. Metode penelitian dilakukan dalam bentuk SLR (Systematic Literature Review). Hasil penelitian menunjukkan bahwa terdapat lima belas produk biosimilar yang berpotensi untuk dikembangkan di Indonesia sebagai pengobatan penyakit tidak menular, diantaranya adalah bevacizumab, trastuzumab, pegfilgrastim, filgrastim, epoetin alfa, insulin glargine, etanercept, infliximab, rituximab dan adalimumab, teriparatide, follitropin alfa, ranibizumab, somatropin dan IFN beta 1-α. Masing-masing produk biosimilar tersebut digunakan untuk pengobatan kanker paru-paru, kanker payudara HER-2 positif, neutropenia, anemia akibat penyakit ginjal kronik, diabetes melitus, rheumatoid arthritis, osteoporosis, infertilitas, degenerasi makula terkait usia neovaskular, defisiensi hormon pertumbuhan dan sklerosis multipel.